Keanekaragaman Jenis Ikan Di Perairan Rawa Dogamit Taman Nasional Wasur Merauke - Stenly Maloky; Norce Mote; Edy H.P Melmambessy (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Dogamit Swamp is one of the swamps in the Merauke Wasur National Park, which stores an abundant diversity of fish and biota. This study aims to examine the diversity of fish species in the waters of Rawa Dogamit. The research was conducted from July to August. The method of data collection was by determining 3 locations of observation stations, at each station an identification of all species and their environmental factors was then linked to the Diversity index, Abundance Index, Evenness Index, and Dominance. The results obtained from the study are that there are 15 species of fish, which have the highest abundance of Betik (Anabas testudineus) by 35.74% and the lowest is the Moon Fish (Megalops cyprinoides) by 0.05%. Measurement of the Diversity index is categorized as moderate, whereas for the Evenness index is categorized high at stations I and II, while station III is categorized as moderate. For the measurement of the Dominance Index, it is categorized as low or not dominant. It was concluded that there was a significant relationship between the diversity, evenness and dominance index with environmental parameters both for the survival of fish in Rawa Dogamit waters.Key Words: Diversity; Fish; Dogamit Swamp